Association between screen time, including that for smartphones, and overweight/obesity among children in Japan: NICE EVIDENCE Study 4 - Izumi Ikeda; Kazuya Fujihara; Sakiko Morikawa Yoshizawa; Yasunaga Takeda; Hajime Ishiguro; Mayuko Yamada Harada; Chika Horikawa; Yasuhiro Matsubayashi; Takaho Yamada; Yohei Ogawa; Hirohito Sone (Endocrine Journal)
The association between screen time (ST), including that for smartphones, and overweight/obesity in children was examined separately for boys and girls, considering the influence of lifestyle factors. A cross-sectional study was conducted in 2,242 Japanese children (1,278 girls) aged 10–14 years. Overweight/obesity was defined by the International Obesity Task Force. Logistic regression analysis showed that only for girls, total ST (≥4 h), smartphone ST (≥3 h), and non-smartphone ST (≥2 h) were all independently and significantly associated with overweight/obesity compared to <2 h total ST, non-use of smartphones, and <1 h non-smartphone ST. Thus, smartphone ST ≥3 h and non-smartphone ST ≥2 h were additively associated with overweight/obesity in girls only. Girls having smartphone ST ≥3 h and non-smartphone ST ≥2 h were 6.79 times (95% CI: 3.11–14.81) more likely to have overweight/obesity than girls with less usage of both. In girls, when total ST was ≥4 < 5 h or smartphone ST was ≥2 h, the significant association with overweight/obesity disappeared when physical activity was ≥60 min/day and sleep time was ≥8.5 h. In addition, none of these associations was significant in boys. In Japanese girls, smartphone ST, non-smartphone ST, and total ST were all significantly associated with overweight/obesity. To avoid overweight/obesity, it is suggested to keep smartphone ST, non-smartphone ST, and total ST to <3 h, <2 h, and <4 h, respectively, and to engage in sufficient physical activity and sleep time.